Trade Liberalization, Selection and Technology Adoption with Vertical Linkages - Antonio Navas; Antonella Nocco (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper analyses the role played by vertical linkages on the effects of trade liberalization on technology adoption and their consequences on average productivity and welfare in a trade model with heterogeneous firms. We find that the strength of vertical linkages shapes the effects that trade liberalization produces on firms' survival and technology upgrading decisions, having an impact on the average productivity of the economy and, ultimately, on welfare.
Keywords: F10; 330; trade liberalization; heterogeneity; selection; technology adoption; vertical linkages